Feeding Practices of School-aged Children during COVID-19 Pandemic: A Qualitative Study - Khoirun Nisa Alfitri; Judhiastuty Februhartanty; Fariz Nurwidya (Amerta Nutrition, 2022)
Background: Coronavirus disease-19 (COVID-19) pandemic caused the government to implement social movement restrictions affecting the household economy and school closure that will lead to change in the home food environment, parental feeding practices, and the end will influence child’s eating behavior. Objectives: This study aimed to explore the parental feeding practices among young school-aged children during the COVID-19 pandemic. Methods: Eighteen informants consisting of mothers and a grandmother have participated in the online in-depth interview. Moreover, 4 fathers had also been interviewed to triangulate the data and to increase the meaningful insight. A question guideline was used to guide the in-depth interview process. Thematic analysis using an inductive approach was applied to analyze the transcripts. Results: Five themes were identified around changes in food restriction, pressure to eat, giving the explanation, child involvement, and modeling. Conclusions: During the COVID-19 pandemic, parents demand their children to have good eating behavior. However, they tend to give autonomy more often to their child to get the snacks. It would make the children lead to having poor and unhealthy eating behaviors.